A DNA Origami Nanorobot Controlled by Nucleic Acid Hybridization. Issue 14 (20th March 2014) - Torelli, Emanuela; Marini, Monica; Palmano, Sabrina; Piantanida, Luca; Polano, Cesare; Scarpellini, Alice; Lazzarino, Marco; Firrao, Giuseppe
<x xml:space="preserve">Abstract</x> A prototype for a DNA origami nanorobot is designed, produced, and tested. The cylindrical nanorobot (diameter of 14 nm and length of 48 nm) with a switchable flap, is able to respond to an external stimulus and reacts by a physical switch from a disarmed to an armed configuration able to deliver a cellular compatible message. In the tested design the robot weapon is a nucleic acid fully contained in the inner of the tube and linked to a single point of the internal face of the flap. Upon actuation the nanorobot moves the flap extracting the nucleic acid that assembles into a hemin/G‐quadruplex horseradish peroxidase mimicking DNAzyme catalyzing a colorimetric reaction or chemiluminescence generation. The actuation switch is triggered by an external nucleic acid (target) that interacts with a complementary nucleic acid that is beard externally by the nanorobot (probe). Hybridization of probe and target produces a localized structural change that results in flap opening. The flap movement is studied on a two‐dimensional prototype origami using Förster resonance energy transfer and is shown to be triggered by a variety of targets, including natural RNAs. The nanorobot has potential for in vivo biosensing and intelligent delivery of biological activators.